Cone Beam CT Evaluation of Maxillary Sinus Septa Prevalence, Height, Location and Morphology in Children and an Adult Population - Orhan, Kaan (Med Princ Pract, 2012)
OBJECTIVE: The purpose of this study was to determine the prevalence, height, location and morphology of maxillary sinus septa in dentate, partially dentate and edentulous adults as well as in mixed dentition children using cone beam computed tomography (CBCT) for maxillary sinus surgical interventions. SUBJECTS AND METHODS: Five hundred and fifty-four sides in the CBCT scans of 272 patients (30 children and 242 adults) were retrospectively analyzed. The prevalence, location and morphology were assessed in axial, sagittal, cross-sectional and panoramic 3-dimensional images. The height of septa was measured with the angle between the direction of the septum and median palatine suture. The differences among age, localization and measurements were statistically analyzed. RESULTS: The prevalence of maxillary sinus segments with septa was 58%. There were a total of 13 (3.2%) septa of completely edentulous (CE), 198 (53.9%) septa of edentate and 14 (3.8%) septa of the mixed dentition maxillary segments. The location of septa observed in all study groups demonstrated a greater prevalence (69.1%) in the middle region than in the anterior and posterior regions. No statistically significant differences were observed with regard to gender or age, for septum height (p > 0.05). However, maxillary sinus septa are higher in partially edentulous patients than edentate and CE ones (p < 0.05). CONCLUSION: Septa of various heights and courses developed in all parts of the maxillary sinus, therefore to prevent possible complications during sinus surgery, extensive evaluation with an appropriate radiographic technique was indispensable.